The Increasing Importance of How We Think of the “Others” During a Time of Uncertainty - Stewart, Tomm; Rantajääskö-Seauve, Hillamaria (International Dialogues on Education Journal, 2020)
This article presents one of the current and evolving societal challenges during the time of Covid-19 crisis and uncertainty: equity in education. Equal opportunities and how we think of the “other” play a vital role on maintaining a stable society. Transformative learning opportunities develop intercultural competencies and cultural proficiency. Finally, a process model for the Development of Intercultural Competencies is presented, accompanied by a table of functional factors completing the model.